Legal Protection of Outsourced Workers Under Indonesia’s Job Creation Law: Between Labor Market Flexibility and Workers’ Rights - Caca Marwan; Abu Nawas; Rasman Habeahan (UIN Jakarta, 2026)
This study examines the legal protection afforded to outsourced workers under Indonesia’s Job Creation Law and its implementing regulations. The enactment of Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law on Job Creation has significantly transformed Indonesia’s labor law framework, particularly in relation to outsourcing practices. One of the most substantial regulatory changes is the removal of restrictions on the categories of work that may be outsourced, which were previously governed under Law Number 13 of 2003 concerning Manpower. The technical implementation of outsourcing arrangements is further regulated under Government Regulation Number 35 of 2021. This research employs a normative legal research method using statutory, conceptual, and comparative approaches. The study is based on the analysis of primary, secondary, and tertiary legal materials, which are examined qualitatively to evaluate the effectiveness of legal protection mechanisms for outsourced workers within the current labor law regime. The findings reveal that the post-Job Creation regulatory framework reflects a paradigm shift from restricting outsourcing practices toward emphasizing normative labor protection. Legally, outsourced workers continue to receive recognition of fundamental labor rights, including wage protection, social security, occupational health and safety guarantees, and compensation rights under fixed-term employment agreements. However, the elimination of limitations on outsourced work has expanded labor market flexibility and increased the potential use of outsourcing systems, which may consequently weaken job security and employment stability for workers. Furthermore, the trilateral legal relationship among outsourced workers, outsourcing service providers, and user companies continues to create legal ambiguities regarding responsibility and accountability in cases involving violations of workers’ rights. This study concludes that although legal protection for outsourced workers is normatively guaranteed under the Job Creation legal framework, its practical effectiveness remains highly dependent on consistent supervision, effective law enforcement, and regulatory compliance by employers. Therefore, a balanced regulatory model is necessary to harmonize economic flexibility with the protection of workers’ fundamental rights within Indonesia’s industrial relations system. Keywords: Outsourced workers; legal protection; labor law; Job Creation Law; industrial relations; labor deregulation; employment security; Indonesia.